2018
DOI: 10.1016/j.conbuildmat.2018.09.194
|View full text |Cite
|
Sign up to set email alerts
|

Determination of water permeability for a moisture transport model with minimized batch effect

Abstract: Values of water permeability for cementitious materials reported in the literature show a large scatter. This is partially attributed to the fact that materials used in different studies are different. To eliminate the effects of cements, specimen preparation, curing conditions and other batch effects, this study employs a long cylindrical cement paste to prepare all specimens for a variety of permeability determination methods, such as beam bending, sorptivity, Katz-Thompson and Kozeny-Carman equations. Perme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 82 publications
(174 reference statements)
0
11
1
Order By: Relevance
“…The first linear stage follows the results of conventional single-porosity model, while the second linear stage deviates from the first linear stage, which is why such a mass change curve is called anomaly. Some other studies reported the anomalous mass change curves which follow the fourth root functions (e.g., Alderete et al 2020), which is certainly different from the most data reported in the literature (Hall et al 1995;Zhou et al 2017;Zhang and Scherer 2018).…”
Section: Introductioncontrasting
confidence: 71%
“…The first linear stage follows the results of conventional single-porosity model, while the second linear stage deviates from the first linear stage, which is why such a mass change curve is called anomaly. Some other studies reported the anomalous mass change curves which follow the fourth root functions (e.g., Alderete et al 2020), which is certainly different from the most data reported in the literature (Hall et al 1995;Zhou et al 2017;Zhang and Scherer 2018).…”
Section: Introductioncontrasting
confidence: 71%
“…It has been argued that the measured mass loss alone is not sufficient to identify parameters in the moisture transport model, in particular for models with more than one parameter [18,39]. This is supported by a recent study [40], which has five parameters to be determined.…”
Section: Validation Datamentioning
confidence: 97%
“…In this study, we consider the heterogeneity of concrete microstructure, so K l as a function of porosity is resealable to assume. Following with previous studies [28,54], the Kozeny-Carman (KC) equation is used to calculate K l based on porosity.…”
Section: ∂S ∂Tmentioning
confidence: 99%